Development of a penem antibiotic against Mycobacteroides abscessus - Hunter R. Batchelder (Nature Portfolio, 2020)
Batchelder et al. report a new penem class antibiotic, T405, which exhibits potent activity against M. abscessus and clinical isolates from cystic fibrosis patients. The development of resistance to T405 is inhibited with the addition of a β-lactamase inhibitor, avibactam. Its clinical potential is further demonstrated by T405 displaying a favourable pharmacokinetic profile in mice with an absence of toxicity.